Interpretation of land use and land cover changes at different classification levels: The Paranapanema River Basin-Brazil case - Manzione, Rodrigo Lilla [UNESP] (Elsevier, 2024)
The MapBiomas project is a multi-disciplinary called effort from NGOs, universities, and technology start-ups to map Land Use and Land Cover (LULC) for the Brazilian territory at annual basis using Landsat archive and random forest classification via Google Earth Engine. This is the most comprehensive and detailed mapping for Brazil at a 30m pixel resolution. However, depending on the level from which the LULC analysis starts, the results can lead to different interpretations. This study analyzed LULC changes in the Paranapanema River Basin (PPRB) region in Brazil from 1990 to 2020, at four MapBiomas classification levels. At Level 1, the LULC change is relatively stable during the period. However, at Level 2, 3 and 4, other LULC change patters appears, indicating important changes in water requirement and consumption in the region. Most of the pasture areas were converted into sugarcane and soybeans crops. In addition, LULC was evaluated at hydrological Planning Units (HPU) level, revealing where and when these land use changes were more intensive in this 30years window. The results indicated the potential of MapBiomas to provide LULC data for detailed analysis at HPU scale and support future studies about the consequences of these LULC changes.
Keywords: Forest formation; Hydrographic planning unit; MapBiomas; Pasture; Soybeans; Sugarcane